2021
DOI: 10.1152/ajplung.00547.2020
|View full text |Cite
|
Sign up to set email alerts
|

Implications of preexisting asthma on COVID-19 pathogenesis

Abstract: The coronavirus disease 2019 (COVID-19) pandemic spreading at an alarming rate has taken a heavy toll on the public healthcare systems and economies worldwide. An abnormal and overactivated inflammatory response is occasionally elicited by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and this hyperinflammation is associated with worse prognosis of COVID-19. Theoretically, one would expect asthma patients to be at a greater risk of SARS-CoV-2 infection considering their increased susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 118 publications
0
25
0
10
Order By: Relevance
“…Asthma can be triggered exacerbation by respiratory viruses, inducing the severity of the infectious condition [67] , but we found the association of asthma with the protective risk for mortality among coronavirus disease 2019 patients. At the same time, the detailed mechanisms of the association between asthma and the risk for COVID-19 mortality are unclear due to several hypotheses taken willingly to accept: (1) asthma in COVID-19 patients may take caution to build a fence to isolate themselves from the crowd and get more medical care from the paramedical practice; (2) the use of medicine to cope with asthma in convention, allergen immunotherapy, inhaled corticosteroids and biological agents, may resist the severe prognoses of COVID-19 in term of suppressing viral replication and relieving inflammation [68] ; (3) type 2 immune response modulating the expression of ACE2 and TMPRSS2 further supports an important role in inflammatory process in COVID-19 pathogenesis [69] .…”
Section: Discussionmentioning
confidence: 99%
“…Asthma can be triggered exacerbation by respiratory viruses, inducing the severity of the infectious condition [67] , but we found the association of asthma with the protective risk for mortality among coronavirus disease 2019 patients. At the same time, the detailed mechanisms of the association between asthma and the risk for COVID-19 mortality are unclear due to several hypotheses taken willingly to accept: (1) asthma in COVID-19 patients may take caution to build a fence to isolate themselves from the crowd and get more medical care from the paramedical practice; (2) the use of medicine to cope with asthma in convention, allergen immunotherapy, inhaled corticosteroids and biological agents, may resist the severe prognoses of COVID-19 in term of suppressing viral replication and relieving inflammation [68] ; (3) type 2 immune response modulating the expression of ACE2 and TMPRSS2 further supports an important role in inflammatory process in COVID-19 pathogenesis [69] .…”
Section: Discussionmentioning
confidence: 99%
“…Higher percentages of circulating Th2 cells were found in the patients with M.tuberculosis infection compared to the controls [ 49 , 50 ]. Within different autoimmune disorders, the majority of patients with asthma demonstrated a predominantly Th2 immune response [ 51 ]. Previous investigations have demonstrated that allergen provocation of the upper and lower respiratory tract inducing allergic airway inflammation leads to a significant decrease in ACE-2 expression, suggesting a possible relationship between allergic inflammation and a lower susceptibility to SARS-CoV-2 infection [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, circulating soluble ACE2, which is upregulated in asthma, could act as a competitive interceptor, limiting the ability of SARS-CoV-2 to bind to airway cell membranes. In patients with Th2-high inflammation, ACE2 gene expression is downregulated [ 4 , 57 , 58 ]. Analysis of nasal airway transcriptome data from 695 children demonstrated that TMPRSS2 is highly upregulated by Th2 inflammation through the action of IL-13 [ 59 ].…”
Section: Asthma Phenotype and Covid-19mentioning
confidence: 99%